STRATEGI PENINGKATAN MUTU DI SEKOLAH DASAR NEGERI DI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - POPI ASTARI; CASKA CASKA; MARZUKI MARZUKI (Universitas Riau, 2017)
Research goal is to provide recommendations to the principal policy strategybasic state in singingihilir district kuantansingingi, with subfokus: (1) Strengths andWeaknesses factors that held in primary SingingiHilir quality improvement in schools (2)Opportunity and Threat factors owned primary schools SingingiHilirKuantanSingingi inschool improvement, (3) strategies used to improve the quality of primary school educationin singingihilir. This study uses swot analysis with qualitative approach. This studyconducted in 19 primary schools in SingingiHilir. The results showed that the school hasstrengths and weaknesses and the opportunities and threats in an effort to improve thequality of education, as for short-term strategy WO : (1) complementary facilities andinfrastructure in accordance with government regulations, (2) complete media learning,(3) professionalism and improving the quality of human resources schools, (4) increasingnumber of employees, (5) optimization of resources to increase the effectiveness ofeducation professional organizers. Long-term strategy for the best, (1) improving academicqualifications human resources with scholarships and tasks learning from government,(2) formulating programs principal and syllabus, plan learning process in accordancewith regulation and state school, (3) building activity education partnership with variousparties, (4) mutual assistance and kinship can maximize the school activities for theimplementation of education, (5) improving the quality of principal and teachers, (6)maximize the functions of facilities and infrastructure in accordance with existingprovisions.